(untitled) (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article emphasizes that today offenses, the fight against crime and their prevention are one of the most important tasks for all states, the prevalence of this crime, and not the punishment of persons who committed the crime of interfering in the investigation or resolution of court cases. According to the analysis of the results of a social survey among judges, law enforcement officers, faculty, lawyers and students, respondents were informed about the need to carry out preventive measures to prevent this category of crimes through systematic analysis and conclusions about their decisions.